Supporting Proliferation of Academic Research - NA Jafarey (ziauddin University, 2024)
Among Universities, Ziauddin University is a fledgling-only 17years old. It started with a Medical Faculty offering MBBS at the undergraduate level and M.Phil/Ph.D at the graduatelevel. The purpose of starting a graduate programme from the very beginning was to build up a junior Faulty of our own. Like so many other places around the world, when we started in 1996 there was an acute shortage of teachers in the Basic Science subjects- a shortage whichstill persists. So it was decided that all the instructors be recruited as graduate candidates after appearing in a written test and interview. This paid off in two ways. Firstly, we had a motivated and committed junior faculty who were interested in teaching as a career and not just a stop gap job-which is what is happening in other medical colleges of the country. Secondly, it laid the foundations of a research group and culture in the University.